2021
DOI: 10.1039/d1bm01233a
|View full text |Cite
|
Sign up to set email alerts
|

An aluminum lining to the dark cloud of silver resistance: harnessing the power of potent antimicrobial activity of γ-alumina nanoparticles

Abstract: Although a biologically nonessential element in living organisms, aluminum is notably nontoxic to eukaryotic cells and has a venerable history of medicinal use. We demonstrate that polyethylene glycol-coated γ-alumina nanoparticles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…We then investigated whether (BiO) 2 CO 3 NPs were active against a strain of methicillin-susceptible Staphylococcus aureus (MSSA; ATCC 6538) and a strain of methicillin-resistant Staphylococcus aureus (MRSA; ATCC BAA 44)—gram-positive bacteria that are prone to developing mupirocin and fusidate resistance. Incidentally, we found that AgNPs are completely ineffective against SA bacteria in our studies (MIC > 900 µg/mL) [ 6 , 19 ], while none of the earlier studies have provided evidence that (BiO) 2 CO 3 NPs could be active against any gram-positive bacteria [ 20 , 21 ]. Our results showed that (BiO) 2 CO 3 NPs exhibit a MIC of 2.0 µg/mL against both DSSA and MRSA ( Table 1 and Figure S2b ), confirming that (BiO) 2 CO 3 NPs possess broad-spectrum antibacterial activity.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…We then investigated whether (BiO) 2 CO 3 NPs were active against a strain of methicillin-susceptible Staphylococcus aureus (MSSA; ATCC 6538) and a strain of methicillin-resistant Staphylococcus aureus (MRSA; ATCC BAA 44)—gram-positive bacteria that are prone to developing mupirocin and fusidate resistance. Incidentally, we found that AgNPs are completely ineffective against SA bacteria in our studies (MIC > 900 µg/mL) [ 6 , 19 ], while none of the earlier studies have provided evidence that (BiO) 2 CO 3 NPs could be active against any gram-positive bacteria [ 20 , 21 ]. Our results showed that (BiO) 2 CO 3 NPs exhibit a MIC of 2.0 µg/mL against both DSSA and MRSA ( Table 1 and Figure S2b ), confirming that (BiO) 2 CO 3 NPs possess broad-spectrum antibacterial activity.…”
Section: Resultsmentioning
confidence: 76%
“…41-1488 [ 15 ]. Subsequently, (BiO) 2 CO 3 NPs were produced by sonicating this phase-pure bulk sample for 18 h using polyvinylpyrrolidone (MW = 8000 g/mole, PVP-8k) as a surface modifier and dimethyl sulfoxide (DMSO) as a solvent [ 6 ]. Transmission electron microscopy (TEM) studies revealed that these NPs have an average size of 5.35 ± 0.82 nm ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1†). 29 This phase-pure bulk powder was then sonicated for 18 h in the presence of polyvinylpyrrolidone (MW avg = 8000 g mol −1 , PVP-8k) and dimethyl sulfoxide (DMSO), yielding the final α-Bi 2 O 3 NPs. To confirm the phase-purity of this product, the powder X-ray diffraction (PXRD) pattern was measured and compared with that of a simulated α-Bi 2 O 3 pattern (ICSD 15072).…”
Section: Resultsmentioning
confidence: 99%